Shassfix Sdn Bhd: Coconut Milk Extractor / Aiman Hakim Badrul Hisham... [et al.] - Badrul Hisham, Aiman Hakim; Mohd Norezan, Mohammed Haniff; Muhammad Sofian, Muhammad Khaizuran Syahmi; Naim, Muhammad Syahiid; Norafandi, Nur Sabrina (2019)
SHASSFIX SON BHO offers sell and repair coconut milking machine products and services for customers, providing the variety coconut milking machine that gives high satisfaction of consumer. Our client is customers identifying as middle and low class who want consume product with affordable price of product. We also targeting busiest workers because we have delivery services of our product to customer home. SHASSFIX SON BHO offers a variety of wheelchair that give customers option to buy the coconut milking machine based on their requirement.